(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the impact of artificial intelligence (AI)–based tools on learners’ motivation in the process of language learning. With the rapid development of digital technologies, AI-powered applications such as chatbots, intelligent tutoring systems, and adaptive learning platforms have become widely used in foreign language education. The study focuses on how these tools influence learners’ intrinsic and extrinsic motivation. The findings suggest that AI-based tools increase learner engagement, autonomy, and interest, which positively affects motivation. The article also discusses potential challenges and pedagogical implications for language teachers.